Survei Kepuasan Pengguna terhadap Kualitas Layanan Sirkulasi di Perpustakaan Umum Daerah Provinsi DKI Jakarta - Khoirunissa, Neyla Raihan; Erwina, Wina; Rohman, Asep Saeful (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2023)
This study aims to determine and analyze user satisfaction with the quality of circulation services at the DKI Jakarta Provincial Public Library based on user’s minimum expectations, ideal expectations, and perceptions. The survey was conducted on 100 respondents who met in the circulation service section. Measurement of service quality using the LibQUAL +TM model by paying attention to 3 dimensions of service, namely: Affect of Service (AS), Information Control (IC), and Library as Place (LP). The research data were analyzed using a gap analysis between user expectations and perceptions. The results showed that in general, circulation services in this library have not been able to meet the minimum expectations of users. The gap analysis on each dimension shows that users are quite satisfied with the Library as Place dimension. Meanwhile, users are not satisfied with the dimensions of Affect of Service and Information Control.